Global Commitment or Local Grievances? An Assessment of the Grundfos Language Policy - Tange, Hanne (HERMES - Journal of Language and Communication in Business, 2008)
This empirical study discusses language workers’ involvement with and responses to the introduction of a corporate language policy at the Danish multinational Grundfos in April 2004. The core argument is that a discrepancy exists between language workers’ global commitment to language management and respondents’ local practices. The analysis explores this differentiation in relation to the themes of language value, language visibility, and the visibility of the corporate language policy, comparing the conﬂ icting views of respondents from management, communications, branding, technical marketing, production, and development units. This leads to the conclusion that the effect of the corporate language initiative is closely related to language attitudes in the different parts of the organisation, which calls for a research perspective that may accommodate local as well as global concerns.